2022
DOI: 10.1038/s41598-022-24711-7
|View full text |Cite
|
Sign up to set email alerts
|

Local-scale feedbacks influencing cold-water coral growth and subsequent reef formation

Abstract: Despite cold-water coral (CWC) reefs being considered biodiversity hotspots, very little is known about the main processes driving their morphological development. Indeed, there is a considerable knowledge gap in quantitative experimental studies that help understand the interaction between reef morphology, near-bed hydrodynamics, coral growth, and (food) particle transport processes. In the present study, we performed a 2-month long flume experiment in which living coral nubbins were placed on a reef patch to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Aragonite saturation, temperature, and oxygen will, however, not vary regularly on length scales at which regular patterns are found in this study, so these environmental factors are unlikely explanations for the observed patterns. Currents and organic matter availability are important for cold‐water coral occurrence (da Costa Portilho‐Ramos et al, 2022; De Clippele et al, 2021) but are also modified by coral reef presence, as demonstrated by observational, experimental, and modeling studies (e.g., Bartzke et al, 2021; Corbera et al, 2022; Davies et al, 2009; Soetaert et al, 2016; Wagner et al, 2011). We suggest that the regular patterns found in the cold‐water coral reefs at the Logachev cold‐water coral mound province are the result of self‐organization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aragonite saturation, temperature, and oxygen will, however, not vary regularly on length scales at which regular patterns are found in this study, so these environmental factors are unlikely explanations for the observed patterns. Currents and organic matter availability are important for cold‐water coral occurrence (da Costa Portilho‐Ramos et al, 2022; De Clippele et al, 2021) but are also modified by coral reef presence, as demonstrated by observational, experimental, and modeling studies (e.g., Bartzke et al, 2021; Corbera et al, 2022; Davies et al, 2009; Soetaert et al, 2016; Wagner et al, 2011). We suggest that the regular patterns found in the cold‐water coral reefs at the Logachev cold‐water coral mound province are the result of self‐organization.…”
Section: Discussionmentioning
confidence: 99%
“…With their dendritic skeletons, corals attenuate and slow down the currents around, within, and behind a coral patch, thus promoting turbulence in their lee (Bartzke et al, 2021; Hennige et al, 2021; Mienis et al, 2019). These flow modifications increase the rate at which coral polyps can filter food particles from the water column (Corbera et al, 2022; Hennige et al, 2021) and increase sediment deposition within the patch, stabilizing the coral framework and stimulating coral reef formation (Bartzke et al, 2021; Douarin et al, 2014; Wang et al, 2021). Downstream of a coral reef, the water is depleted of food particles (Corbera et al, 2022; Wagner et al, 2011), and around a coral reef, erosive scouring can negatively affect reef formation (Huvenne et al, 2009; Lim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local flow regime of a CWC reef habitat is influenced not only by seabed topography, but also by the corals themselves, which are capable of significantly altering the surrounding flow field with their complex structure, deflecting near-bed flow and decreasing turbulence and current speed in their wake (Mienis et al 2019;Bartzke et al 2021;Hennige et al 2021;Corbera et al 2022). This suggests that CWC colonies can mutually influence each other's morphology, by inducing heterogeneous flow patterns that may increase local architectural variability.…”
Section: Environmental Influence On Cwc Architecturementioning
confidence: 99%
“…In principle, more compact D. pertusum colonies intercept sinking and transported sediment more effectively and require a lower amount of infill, becoming buried more rapidly and thus enhancing reef and mound growth rates under suitable sediment supply conditions (Wang et al 2021). CWC growth, hydrodynamics and sedimentation are mutually influenced at multiple scales, with development of colonies, reefs and mounds enhancing flow, food supply to living colonies and sediment baffling by dead framework, and thus further growth (Masson et al 2003;Davies et al 2009;Buhl-Mortensen et al 2016;van der Kaaden et al 2021;Corbera et al 2022). The high sensitivity of CWC architecture to water flow may further boost this positive feedback mechanism, with exposure of elevated colonies to stronger currents (and enhanced food supply) resulting in higher compactness, which would in turn facilitate post-mortem sedimentary infilling.…”
Section: Ecosystem Significance Of Cwc Architectural Variationmentioning
confidence: 99%